Twelve polymorphic microsatellite loci developed and optimized from the Leptodactylus chaquensis - Arruda, Mauricio P. [UNESP]; Morielle-Versute, Eliana [UNESP]; Silva, Artur; Cruz Schneider, Maria Paula; Goncalves, Evonnildo C. (Springer, 2010)
We isolated and characterized twelve polymorphic microsatellite loci for Leptodactylus chaquensis. Levels of polymorphism of the microsatellite loci measured in twenty individuals showed two to 7 alleles per locus with observed heterozygosity ranging from 0.20 to 0.75 and polymorphic information content ranging from 0.1736 to 0.7431. No evidence for linkage disequilibrium was detected between all pairs of loci and deviations from Hardy-Weinberg expectations were not significant for any loci. These microsatellite markers reported here can be used in genetic analysis of populations and contribute to a better understanding of the taxonomy of the ocellatus group verifying the occurrence of reproductive isolation of species (or subspecies) closely related to L. chaquensis.
Keywords: Leptodactylus; Leptodactylidae; Microsatellite; Ocellatus group; Population genetic